Effect of Administration of Crystalloid IV Fluids Preoperatively on Postoperative Pain - Zeena M. Al-Nema; Samer I. Mohammed; Fadia T. Ahmed (College of Pharmacy University of Baghdad, 2017)
Pain is a sensory and emotional experience that is influenced by physiologic, sensory, affective, cognitive, socio-cultural and behavioral factors. Postoperative pain is the commonest reason for delayed discharge and unanticipated hospital admission after ambulatory surgery. Our Objective is to test the hypothesis that administration of 2 ml/kg/hr preoperative IV fluids may attenuates postoperative pain.The study was carried out in the Baghdad Teaching Hospital, Al-Yarmok Teaching Hospital and Al-Karama Teaching Hospital from 12 May till 17 June 2009. The total number of patients was 120 (35 males and 85 females) with their age ranged between 10-90 years. The patients were divided into two groups according to administration of preoperative IV fluids, group A (65 patients) did not receive IV fluids and group B (55 patients) received IV fluids preoperatively. Regarding group A, the pain scale was â‰¤ 5 in 15.3% of patients, and it was >5 in 84.7% of patients and these results obtained within 0-5 hours after awaking from anesthesia. Whereas in group B, the pain scale was â‰¤5 in 29.09% of patients and was >5 in 70.9% of patients. We have demonstrated that the preoperative administration of 2ml/kg/hr IV fluids (crystalloid) to patients who had fasted from fluids decreased the severity of postoperative pain, and the need for postoperative analgesia.  We report for the first time that administration of large volume preoperative IV fluids significantly reduce the incidence and severity of pain in patients at high risk for pain. Key words: I.V fluids, Pain, Surgery.